Salih Zeki ve Darülfünun - (:unkn) unknown (My University, 2005)
0

Salih Zeki had a productive life in science, education and philosophy. He wrote textbooks for high schools on algebra, geometry, physics and astronomy between 1882 and 1908. This period refers also to his intensive work on history and philosophy of mathematics when he also realized his major project Kamus-i Riyaziyat, a 12-volume lexicon of mathematical sciences. Starting to lecture on mathematics and physics soon after the establishment of the Darülfünun in 1900, Salih Zeki kept instructing until he died in 1921. During these 20 years at Darülfünun, he gave conferences on different subjects of math, wrote textbooks for university students as well as the Asâr-ı Bâkiye related to the history of mathematics in Islam. Salih Zeki introduced Henri Poincaré by translating his books on philosophy of science. Besides taking charge in the ministry of education, he also participated to the reorganisation of the Darülfünun curriculum. Within this fruitfful life, the article aims to display his relationship with Darülfünun.
Salih Zeki and the Darülfünun
Keywords: Tarih